2023
DOI: 10.3389/fpls.2023.1144748
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of BcGRF genes in flowering Chinese cabbage and preliminary functional analysis of BcGRF8 in nitrogen metabolism

Abstract: Growth-regulating factors (GRFs) are a unique family of transcription factors with well-characterized functions in plant growth and development. However, few studies have evaluated their roles in the absorption and assimilation of nitrate. In this study, we characterized the GRF family genes of flowering Chinese cabbage (Brassica campestris), an important vegetable crop in South China. Using bioinformatics methods, we identified BcGRF genes and analyzed their evolutionary relationships, conserved motifs, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…For instance, in A. thaliana, AtGRF5 and AtGRF6 do not exhibit complementarity to the mature miR396s sequences [1,2,21]. Similarly, homologs of AtGRF5/6 in Brassica campestris and Brassica rapa also lack the conserved "RSRK-VE" motif in their coding sequences and do not have the target binding sites for miR396s [7,14]. Interestingly, OsGRF11 and its homologs ZmGRF4/10 belong to distinct subgroup members of AtGRF5/6 and do not possess the conserved "RSRK-VE" motif either [13,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in A. thaliana, AtGRF5 and AtGRF6 do not exhibit complementarity to the mature miR396s sequences [1,2,21]. Similarly, homologs of AtGRF5/6 in Brassica campestris and Brassica rapa also lack the conserved "RSRK-VE" motif in their coding sequences and do not have the target binding sites for miR396s [7,14]. Interestingly, OsGRF11 and its homologs ZmGRF4/10 belong to distinct subgroup members of AtGRF5/6 and do not possess the conserved "RSRK-VE" motif either [13,48].…”
Section: Discussionmentioning
confidence: 99%
“…The WRC domain is considered to function in the DNA-binding process due to the containing of a putative nuclear localization signal and a C3H-type zinc (Zn) finger motif [3,5]. Moreover, the WRC domains in most plant GRFs contain a conserved "RSRK-VE" motif at its terminus, which corresponds to a nucleotide sequence that complements the mature miR396 sequences [6,7]. Numerous studies have unequivocally demonstrated that miR396 can bind to its target sites on GRF to negatively regulate the expression of the GRF gene [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation